2016
DOI: 10.1007/s11738-016-2069-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamates from elecampane (Inula helenium L.) callus culture

Abstract: Hydroalcoholic extract from Inula helenium callus tissue showed remarkable reducing capacity. An HPLC/DAD analysis revealed the presence of numerous hydroxycinnamic acid derivatives, including chlorogenic acid (5-O-CQA, 0.1 % dry weight) and 3,5-dicaffeoylquinic acid (3,5-DCQA, 0.3 % dry weight), which were among major constituents of the examined extract. Application of a hyphenated chromatographic method-UHPLC/DAD/MS n -allowed identification of sixteen compounds, derivatives of caffeic acid. Apart from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Peaks 4, 10, 13, 14 and 16, representing compounds which showed cleavage of two, three or four caffeoyl [M − H − (2–4 × 162)] − moieties resulting in m / z 209 fragments, were assigned to hexaric acid derivatives: di- O caffeoylhexaric acid (peak 4), tri- O -caffeoylhexaric acid (I) (peak 10), tri- O -caffeoylhexaric acid (II) (peak 13), tri- O -caffeoylhexaric acid (III) (peak 14) and tetra- O -caffeoylhexaric acid (peak 16). The compounds have been described earlier as constituents of other plants of the Asteraceae family, including systematically related species Inula helenium and Carpesium divaricatum [ 10 , 11 , 12 , 13 ]. The compound represented by peak 12 was an unknown derivative of dicaffeoylquinic acid judging from the presence of fragmentation ions at m / z 353, 335 and 179.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks 4, 10, 13, 14 and 16, representing compounds which showed cleavage of two, three or four caffeoyl [M − H − (2–4 × 162)] − moieties resulting in m / z 209 fragments, were assigned to hexaric acid derivatives: di- O caffeoylhexaric acid (peak 4), tri- O -caffeoylhexaric acid (I) (peak 10), tri- O -caffeoylhexaric acid (II) (peak 13), tri- O -caffeoylhexaric acid (III) (peak 14) and tetra- O -caffeoylhexaric acid (peak 16). The compounds have been described earlier as constituents of other plants of the Asteraceae family, including systematically related species Inula helenium and Carpesium divaricatum [ 10 , 11 , 12 , 13 ]. The compound represented by peak 12 was an unknown derivative of dicaffeoylquinic acid judging from the presence of fragmentation ions at m / z 353, 335 and 179.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds were identified based on their retention time values, online UV spectra, co-chromatography with standard samples and comparison with the results of HPLC-DAD-MS n analysis. Quantification was done using an external standard method as it was described previously [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peaks 3, 7, and 9, representing compounds that showed a cleavage of two or three caffeoyl [M – H − (2 − 3 × 162)] − moieties resulting in the m / z 209 fragment, were assigned to hexaric acid derivatives: di- O caffeoylhexaric acid (I) (peak 3), tri- O -caffeoylhexaric acid (I) (peak 7), and tri- O -caffeoylheharic acid (II) (peak 9). The compounds have been previously described as constituents of other plants of the Asteraceae family [10,11,12,13], including the systematically related species Inula helenium [14]. Compounds corresponding to peaks 10 and 11 were tentatively identified as isobutyryl-dicaffeoylquinic acids based on the presence of quasimolecular ions at m / z 585 [M − H] − and product ions at m / z 497 [585 − C 3 H 7 COOH] − , 423 [585 − caffeoyl] − , 335 [497 − caffeoyl] − or [423 − C 3 H 7 COOH] − , and 179 [caffeic acid − H] − , which is in accordance with the data given by Heilmann et al [15].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the average contents of 5‐CQA in 33 samples of I. britannica flowers, stems and aerial parts, 6 samples of I. japonica flowers and 6 samples of I. hupehensis flowers from China were found to be 323, 146, 302, 660 and 296 μg/g DM, respectively . The major compounds in I. helenium callus cultures were 3,5‐ and 1,5‐DCQA as well as 5‐CQA (0.259, 0.107 and 0.101 % DW, respectively) . It has been also reported that different extracts from I. helenium roots contained 5‐CQA (35.5–47 mg/100 g DW) and dicaffeoylquinic acid (60.8–73.4 mg/100 g DW) .…”
Section: Resultsmentioning
confidence: 99%
“…Plants belonging to this genus have shown to possess various biological activities–anti‐inflammatory, antitumor, antibacterial, antitussive, antiproliferative, antioxidant, antidiabetic and hepatoprotective, etc., which were attributed to the abundance of bioactive components mainly sesquiterpene lactones, phenolic acids, and flavonoids . Chlorogenic acid and dicaffeoyl esters of quinic acid have been also reported in some Inula species …”
Section: Introductionmentioning
confidence: 92%